2020
DOI: 10.1002/mbo3.1096
|View full text |Cite
|
Sign up to set email alerts
|

Small noncoding RNA sRNA0426 is involved in regulating biofilm formation in Streptococcus mutans

Abstract: Evidence suggests that small noncoding RNAs (sRNAs) are involved in the complex regulatory networks governing biofilm formation. Few studies have investigated the role of sRNAs in Streptococcus mutans (S. mutans). In the present study, the association between sRNA and biofilm formation in S. mutans was explored. sRNAs that are differentially expressed in the biofilm and planktonic states of this bacterium were identified by quantitative real‐time PCR (qRT‐PCR). Confocal laser scanning microscopy was used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Yin et al . detected a potential sRNA regulation pathway in S. mutans by bioinformatics technology [ 52 ]. The results showed that sRNA0426 has a strong positive relationship with the dynamic biofilm formation in S. mutans .…”
Section: Regulation Of S Mutans Biofilm Formation ...mentioning
confidence: 99%
“…Yin et al . detected a potential sRNA regulation pathway in S. mutans by bioinformatics technology [ 52 ]. The results showed that sRNA0426 has a strong positive relationship with the dynamic biofilm formation in S. mutans .…”
Section: Regulation Of S Mutans Biofilm Formation ...mentioning
confidence: 99%
“…(2019) Bacillus subtilis RsaE regulates PIA mediated biofilms Schoenfelder et al. (2019) Streptococcus mutans FasX inhibits collagen-binding pilus and biofilm ( Liu et al., 2012 ; Danger et al., 2015 ) Streptococcus mutans sRNA0426 regulates exopolysaccharide biosynthesis Yin et al. (2020) Streptococcus mutans AS vic R negatively regulates biofilm biomass Lei et al.…”
Section: Biofilm Regulation By Non-coding Rna In Gram-negative Bacteriamentioning
confidence: 99%
“…Bacterial non-coding RNAs (ncRNAs), although not translated into functional proteins, can regulate sensitivity to antibiotics [33,270] as well as biofilm formation [271][272][273][274][275][276], virulence [277][278][279][280][281], and stress responses [280,[282][283][284] by modulating gene expression. Some regulatory ncRNAs (rRNAs) reside in the 5'UTR of the regulated gene and sense the presence of the antibiotics by recruiting translating ribosomes onto short upstream open reading frames embedded in the ncRNA.…”
Section: Involvement Of Non-coding Rnas In Antibiotic Resistancementioning
confidence: 99%